Модeлювання та дослідження міцності продольно армованого елементу фундаменту - Красніков, Сергій Васильович (НТУ "ХПІ", 2015)
Розглядається міцність фундаментів парових турбін. Наведено результати дослідження міцності типового елементу залізобетонного фундаменту. Розглядаються різні варіанти ушкодження арматури залізобетонного елементу. Побудовано дві серії моделей типового елементу. Ушкодження арматури розглядається с двох напрямків – кількісне та якісне. Проведено розрахунки та аналіз параметрів міцності. Було розраховано напруги та переміщення. Більш докладно зроблено аналіз напруг типового елементу. Зроблено висновки з найбільш суттєвих схем ушкоджень арматури. Для моделювання та розрахунків було використано метод скінчених елементів.

Considered the strength of foundations for steam turbines. The results of the research strength of typical elements of the foundation are given. The foundation is the backbone of the steam turbine. Type of build the foundation - reinforced concrete. Various options twisting reinforcement concrete elements. Constructed two series models typical element. The first series models - concrete element models with different details. The second series models - concrete elements with different damage valves. For each series models is the basic design. For the first series design is the most common physical characteristics. For the second series basic model consists of typical concrete and reinforcement. Damage to the fittings look with two directions - quantitative and qualitative. The calculations of stresses, strains, displacements are completted. The analysis of parameters of strength are given. Particular attention is paid tension and displacement. The most detailed analysis done voltages typical element are made. The conclusions of damage valves are done. Make a list of the most significant types of damage valves. Modeling and calculations made with using finite element method.
Study of strength longitudinal reinforced elements of foundation
Keywords: працездатність; напруга; деформація; переміщення; турбіна парова; performance; stress; strain; displacement; steam turbine